2017
DOI: 10.1200/jco.2016.69.5197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Viral Status on Survival in Patients Receiving Sorafenib for Advanced Hepatocellular Cancer: A Meta-Analysis of Randomized Phase III Trials

Abstract: Purpose Following the Sorafenib Hepatocellular Carcinoma Assessment Randomized Protocol (SHARP) trial, sorafenib has become the standard of care for patients with advanced unresectable hepatocellular carcinoma, but the relation between survival advantage and disease etiology remains unclear. To address this, we undertook an individual patient data meta-analysis of three large prospective randomized trials in which sorafenib was the control arm. Methods Of a total of 3,256 patients, 1,643 (50%) who received sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 29 publications
8
89
3
Order By: Relevance
“…On the other hand, the diverse distribution of aetiologic factors across groups might be an equally important factor to underpin such biologic heterogeneity. Interestingly, in our study, we found the PT group to comprise more HCV-related cirrhotics, whose survival was significantly superior to those with other aetiologies, echoing evidence from recently published meta-analyses highlighting improved survival among patients with HCV-associated HCC treated with sorafenib [35]. …”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, the diverse distribution of aetiologic factors across groups might be an equally important factor to underpin such biologic heterogeneity. Interestingly, in our study, we found the PT group to comprise more HCV-related cirrhotics, whose survival was significantly superior to those with other aetiologies, echoing evidence from recently published meta-analyses highlighting improved survival among patients with HCV-associated HCC treated with sorafenib [35]. …”
Section: Discussionsupporting
confidence: 63%
“…The AFP level and macrovascular invasion were not used as independent stratification factors, resulting in an imbalance unfavorable to the lenvatinib group, with a higher number of sorafenib-responsive hepatitis C patients [17] in the sorafenib group. This may be one of the reasons why the superiority of lenvatinib in OS was not verified.…”
Section: Insights Into the Success Of The Reflect Trialmentioning
confidence: 99%
“…It has recently been shown that the impact of sorafenib is largely confined to the patients who are HCV positive [25,26]. The present NMA cannot account for this specific aspect to be ascertained, and the investigation of this issue would require subgroup efficacy and safety data segregated for HCV positive and negative patients.…”
Section: Discussionmentioning
confidence: 99%